Alkyl esters content and other quality parameters in oil mill: A response surface methodology study. Issue 1 (4th July 2016) - Alcalá, Sonia; Ocaña, María Teresa; Cárdenas, José Rafael; Miquel, Miguel Ángel; Vilar, Juan; Espínola, Francisco; Moya, Manuel
Abstract : The quality of the olives oil can be altered during their processing. This paper studies the influence that the washing of olive oils has on their alkyl esters content and on other quality parameters. A Central Composite Rotatable Design (CCRD) with five center points has been used to modify the factors, rotational frequency of the motor of the vertical centrifuge (between 34 and 47 Hz) and percentage of added water (between 6 and 34%). Results show that the content in alkyl esters of olive oils increases by the flow from the decanter to the vertical centrifuge. The use of water in the vertical centrifuge decreases the content in ethyl and methyl esters 0.8 and 0.6 mg/kg, respectively, per percentage unit of added water. The acidity, peroxide index, K 232, chlorophyll, and carotenoid contents are slightly altered by the oil flow from the decanter to vertical centrifuge, but not by operating factors. K 270, total polyphenols and orthodiphenols change with the speed of the vertical centrifuge, but water does not affect them. For the normal operation frequency of the centrifuge (50 Hz), K 270 is increased about 14%, while the total polyphenols and orthodiphenols decrease by 27 and 62%, respectively. Practical applications: Quality control of olive oils (virgin and extra virgin). Olive‐oil production process: differences in the content of EE and TP between the vertical centrifuge way out and the decanter way out. Abstract : Olive‐oil production process: differences in the content of EE and TP between the vertical centrifuge way out and the decanter way out.